The OCB Determinant of Employees in Non-Profit Organization; Leadership Role and Work Engagement - Purwanto, Sigit; Wibowo, Agung; Suharti, Titing (INOVATOR, 2023)
This study aims to examine the effect of transformational leadership behavior, transactional, and work engagement on organizational citizenship behavior (OCB) in the context of non-profit organizations or communities (NPO) in Indonesia. Referring to the judgment sampling technique, the amount of primary data obtained is as many as 120 employees who work at NPO in Bogor, West Java, Indonesia. To verify the research hypothesis, a structural equation modeling technique based on partial least squares was applied. The results show that transformational, transactional leadership, and work engagement affect OCB. The results of this study may be useful for NPO leaders and supervisors, especially regarding the influence of leadership behavior on the work results of human resource assets. Due to the limited amount of research conducted on leadership in non-profit organizations, this research contributes theoretically and empirically to the leadership literature as it is the first study to investigate the two leadership styles on work-related outcomes and work engagement in the non-profit sector.